Application of Cluster Analysis Using Hierarchic Method for Classification of Municipalities/Cities in Kalimantan Based on Socio-Economic Variables - Ananto Wibowo; M. Rismawan Ridha (Matematika: Jurnal Teori dan Terapan Matematika, 2021)
All provinces in Kalimantan show inequality level of income distribution that fluctuate, but some have increased from 2015 to 2018. This study aims to classify the regencies and municipalities based on the conditions of social and economic variables with hierarchical cluster analysis to minimize the disparities between regions. The data source comes from Statistics Indonesia (BPS) in each province of Kalimantan in 2018. The results show a correlation between variables, so that the Mahalanobis Distance application is more appropriate to use than Euclidean Square Distance. We formed three groups of regencies and municipalities based on the cluster analysis results. The first group (the good economic group) consisted of 48 observations, the second group (the good economic and social group) consisted of 7 observations, and there was only one observation in the third group (the good social group). Based on empirical research, we should optimize the focus of development in regencies and municipalities in the first and third groups.